Analisis Pengaruh Variasi Heat Treatment Material Aluminium Alloy 6063 Terhadap Laju Korosi - Asri Dilomo; Priyagung Hartono; Unung Lesmanah (Universitas Islam Malang, 2024)
Corrosion is material damage caused by comprehensive aspects, destruction or damage to the material due to reactions with its environment. Corrosion is a damage to materials (generally metals), the corrosion process occurs not only in the form of chemical reactions, but also electrochemical reactions. In the industrial world, the use of engineering materials is one of the most important for the application of various kinds of equipment, the use of alumininium alloy material which is very widely applied, especially in the development of the automotive sector that requires lightweight materials and is not susceptible to damage caused by corrosion, improving material properties by changing the atomic structure of the material by heat treatment of materials using the precipitation hardening method. Corrosion analysis on aluminum alloy 6063 material using weight loss method according to ASTM G31-72 standard, reweighing material after corrosion on pure seawater media to determine material weight loss caused by seawater